2004
DOI: 10.1248/bpb.27.375
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Rheum Species Used as Rhei Rhizoma Based on the Chloroplast matK Gene Sequence and Its Application for Identification

Abstract: Rhei Rhizoma, called Dahuang in Chinese, is one of the important herbal drugs widely used as a purgative and antiinflammatory agent. In traditional Chinese formulations and over-the-counter drugs, Dahuang is also used for the treatment of oketsu (various syndromes caused by the obstruction of blood circulation such as dysmenorrhea, etc.). 1,2) In the Chinese Pharmacopoeia, 1) the official Dahuang is prescribed for the dried rhizome and root of Rheum palmatum L., R. tanguticum MAXIM. ex BALF., and R. officinale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 8 publications
(5 reference statements)
0
39
0
Order By: Relevance
“…The botanical origins of each sample were correctly identified by the molecular biological methods previously reported. 21,22) The rhubarb sample (Qinghai Prov., TMPW no. 19929) used for the isolation of standard compounds was purchased from Uchida Wakanyaku Co., Ltd. (Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The botanical origins of each sample were correctly identified by the molecular biological methods previously reported. 21,22) The rhubarb sample (Qinghai Prov., TMPW no. 19929) used for the isolation of standard compounds was purchased from Uchida Wakanyaku Co., Ltd. (Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Different molecular techniques were employed to measure the genetic diversity among plant species including some gene specific sequences such as matK, rbcL, ITS regions (Hilu and Liang 1997;Ma and Yin 2009;Cao et al 2001;Koch et al 2001;Zhu et al 2003;Yang et al 2004;Zhang et al 2013;Chen et al 2014;Xing 2014). Recently the high-throughput SNP genotyping techniques based on NGS method are used to analyze the genetic diversity (Kumar et al 2012;Shirasawa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, 13) we investigated the phylogenetic relationship of the Rheum species, especially of R. palmatum, R. tanguticum and R. officinale of section Palmata, used as Rhei Rhizoma officially on the basis of their matK gene sequences. The phylogenetic tree suggested that R. tanguticum and R. officinale were monophyletic, but R. palmatum was mainly composed of 3 groups (I, II, III) which were related to the production area.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one drug sample named "Ya-huang" (D21), which is available in the Japanese market, was found to be derived from group I of R. palmatum, not as expected from group III. 13) Although the Ya-huang samples imported from China have been known to be produced in Jiulong and Shimian Counties, the central part of Sichuan Province, 5,20) their production areas have been moved recently to the northwestern part. In fact, the partial matK gene sequence was found to be identical to that of wild plants from Xinlong County, in the northwestern part of Sichuan Province (Table 2: Ps15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation